Efforts to Increase Student Learning Interest through Group Discussion Methods in Science Learning in Class V of MI Negeri 12 Nagan Raya - Haris Zulvianda (Journal of Indonesian Primary School, 2025)
This research is a Class Action Research (PTK) which aims to increase the learning interest of students in class V of MIN 12 Nagan Raya in science subjects, especially Chain of Meaning materials, through the application of group discussion strategies. The background of this research is based on the low interest of students in social studies lessons which is shown by a lack of activeness in learning, lack of participation in discussions, and low learning outcomes. The research was carried out in two cycles, each consisting of the stages of planning, implementation of actions, observation, and reflection. The research subjects were 25 students of class V. Data collection techniques were carried out through observation, learning interest questionnaires, learning outcome tests, and documentation. Data analysis uses qualitative and quantitative approaches. The results of the study showed a significant increase in students' interest in learning. In the pre-cycle, only 30% of students had a high interest in learning, while after cycle II it increased to 80%. The average learning outcome score also increased from 65 (pre-cycle) to 81 (cycle II). In addition, students' activeness in group discussions also increased significantly. It can be concluded that the group discussion strategy is effective in increasing students' interest and learning outcomes on Food Chain materials. This strategy is also able to create an active, collaborative, and fun learning atmosphere.